Closing the Integration Gap: A Pilot for Incorporating Foundational Sciences, DEI-Decision Making, Empathy, and Communication for Congestive Heart Failure and Arrhythmia Management by Pharmacy Students - Ashim Malhotra; Song Oh; Zhuqiu Jin; Xiaodong Feng (MDPI AG, 2022)
Pharmacists must integrate foundational sciences with pharmacy practice for providing optimal patient care. Pharmacy students need to be trained to provide culturally competent, linguistically accessible, and empathetic care while integrating foundational science principles. However, such holistic integration is challenging to achieve and assess. To bridge this gap, we implemented and assessed an "integrated cardiovascular simulation" (ICS) module for P2 students, employing case-based and team-based learning. ICS focused on congestive heart failure with preexisting arrhythmia and incorporated patient counseling relating to diversity factors such as cultural competency, linguistic challenges, and the impact of population diversity on cardiac diseases. Students learned the SBAR communication technique (situation, background, assessment, and recommendation) and recommended therapy while elaborating on drug MOA and adverse effects. ICS was assessed through pre-and post-session quizzes and perception data immediately after the activity, and after two years, when students progressed to the cardiovascular APPE block. Student performance improved on a post-test (80.2%) compared to the pre-test (66.9%), p < 0.01 paired student t-test, with an increase in symptom and arrhythmia pattern recognition (41.2% and 36.7%, respectively). ICS was effective for teaching (1) arrhythmia pathophysiology (85%), (2) EKG interpretation (89%), (3) drug adverse effects (93%), (4) DEI-clinical decision making (92%), and (5) communication skills (85%).